KIR3DL2 binds to HLA-B27 dimers and free H chains more strongly than other HLA class I and promotes the expansion of T cells in ankylosing spondylitis. - Wong-Baeza, I; Ridley, A; Shaw, J; Hatano, H; Rysnik, O; McHugh, K; Piper, C; Brackenbridge, S; Fernandes, R; Chan, A; Bowness, P; Kollnberger, S (2013)
The human leukocyte Ag HLA-B27 (B27) is strongly associated with the spondyloarthritides. B27 can be expressed at the cell surface of APC as both classical β2-microglobulin-associated B27 and B27 free H chain forms (FHC), including disulfide-bonded H chain homodimers (termed B27(2)). B27 FHC forms, but not classical B27, bind to KIR3DL2. HLA-A3, which is not associated with spondyloarthritis (SpA), is also a ligand for KIR3DL2. In this study, we show that B27(2) and B27 FHC bind more strongly to KIR3DL2 than other HLA-class I, including HLA-A3. B27(2) tetramers bound KIR3DL2-transfected cells more strongly than HLA-A3. KIR3DL2Fc bound to HLA-B27-transfected cells more strongly than to cells transfected with other HLA-class I. KIR3DL2Fc pulled down multimeric, dimeric, and monomeric FHC from HLA-B27-expressing cell lines. Binding to B27(2) and B27 FHC stimulated greater KIR3DL2 phosphorylation than HLA-A3. B27(2) and B27 FHC stimulated KIR3DL2CD3ε-transduced T cell IL-2 production to a greater extent than control HLA-class I. KIR3DL2 binding to B27 inhibited NK IFN-γ secretion and promoted greater survival of KIR3DL2(+) CD4 T and NK cells than binding to other HLA-class I. KIR3DL2(+) T cells from B27(+) SpA patients proliferated more in response to Ag presented by syngeneic APC than the same T cell subset from healthy and disease controls. Our results suggest that expansion of KIR3DL2-expressing leukocytes observed in B27(+) SpA may be explained by the stronger interaction of KIR3DL2 with B27 FHC.